Cyprus : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
KEY ISSUES Background: The large imbalances that accumulated prior to the global financial crisis culminated in a collapse of the banking sector in early 2013. In response, the authorities took unprecedented measures and adopted an economic adjustment program, supported by official financing, aimed at securing financial stability and fiscal sustainability. Recent developments and outlook: GDP contracted sharply in 2013. Wages and prices also declined, and unemployment increased. While bank deposit outflows have slowed, non-performing loans have risen sharply, and credit remains impaired. The outlook is difficult, with the recession expected to continue this year, followed by a modest recovery starting next year. Risks remain tilted to the downside. Reform agenda: The authorities need to overcome recent delays in the implementation of their adjustment program. A key priority is addressing high non-performing loans, which requires putting in place a strong private-sector debt-restructuring framework, including legislation to facilitate foreclosures, complemented by a modernized insolvency regime. Banks should continue to restructure and build strong capital buffers. Removal of external-payment restrictions must proceed prudently. Continued fiscal consolidation is required to ensure long-run sustainability, complemented by firm implementation of structural reforms.